Influence of Step Frequency on Movement Intensity Predictions With the CSA Accelerometer: A Field Validation Study in Children - Brage, S.; Wetterkopp, N.; Andersen, L. B.; Froberg, K. (Pediatric Exercise Science, 2003)
Four Computer Science and Applications (CSA, Model 7164) accelerometers were validated against speed and heart rate in a field trial, consisting of two walking and two preset running speeds, and 3 min of running at freely chosen speeds. Fifteen children (9-11 years) were recruited from a suburban school in Denmark. Mean CSA output was calculated and converted to acceleration by calibration to sinusoidal accelerations in a mechanical setup, the latter variable being independent of frequency-based filtering. Mean CSA output and estimated acceleration both correlated significantly with speed (r2 = 0.55 and r2 = 0.76, respectively) and heart rate (r2 = 0.60 and r2 = 0.81, respectively), controlled for gender. ANOVA post hoc test failed to show significant differences in accelerometer output between running speeds. Inter-individual variability of CSA output and acceleration could not be explained by differences in step frequency in walking but running values correlated significantly with step frequency (r = -0.86 and r = -0.47 for CSA output and acceleration, respectively). Conversion of CSA output to average acceleration provides more precise estimates of intensity with less inter-individual variability than raw CSA output. Different running intensities, however, are generally not well differentiated with vertical accelerometry.